Red to blue emitting cationic iridium complexes with 2-phenyl-4-dimethylaminopyridine as the cyclometalating ligand: Synthesis, characterization and electroluminescent devices. (June 2019) - Meng, Xianwen; Bai, Rubing; Wang, Xiaoxiang; Pan, FangFang; He, Lei
Abstract: 2-Phenyl-4-dimethylaminopyridine (dmappy) with high 3 π-π ∗ triplet energy is, for the first time, employed as the cyclometalating ligand for constructing cationic iridium complexes with tunable emission properties. Three complexes, namely, [Ir(dmappy)2 (bpy)]PF6 (1), [Ir(dmappy)2 (pzpy)]PF6 (2) and [Ir(dmappy)2 (dma-pzpy)]PF6 (3), have been designed and synthesized (bpy = 2, 2′-bipyridine, pzpy = 2-(1 H -pyrazol-1-yl)pyridine and dma-pzpy = 4-dimethylamino-2-(1 H -pyrazol-1-yl)pyridine), and their photophysical and electrochemical properties have been comprehensively investigated. By using ancillary ligands with increasing electron-richness (bpy → pzpy → dmapzpy), complexes 1–3 emit red, green and blue light, respectively. Theoretical calculations reveal that for complexes 1 and 2, the light emission stems predominantly from the charge-transfer states (Ir/dmappy → bpy or pzpy), whereas for complex 3, the light emission originates mainly from the dmappy-centered 3 π-π ∗ state. In the doped film, fluorine-free complex 3 affords comparable emission color, luminescent efficiency and excited-state lifetime to the typical blue-emitting, neutral iridium complex FIrpic that uses fluorinated ligands. Single-layer, solution-processed organic light-emitting diodes based on complex 3 affords blue electroluminescence (EL) peaked at 472 nm, with the EL color competing with that from FIrpic and the peak current efficiency (12.6 cd A −1 ) being among the highest reported for single-layer, solution-processed blue OLEDs based on ionic iridium complexes. Graphical abstract: Image 1 Highlights: 2-phenyl-4-dimethylaminopyridine was tested as a main ligand for cationic Ir complex. Color-tuning from red to blue was achieved by varying the ancillary ligand. The blue-emitting complex showed comparable emission properties to FIrpic. Single-layer solution-processed blue OLED afforded an efficiency of 12.6 cd A −1 .